1, 4-Diazabicyclo[2.2.2]octane-based disalts showing non-centrosymmetric structures and phase transition behaviors. Issue 9 (8th February 2016) - Han, Xiang-Bin; Hu, Pan; Shi, Chao; Zhang, Wen
Abstract : Two 1, 4-Diazabicyclo[2.2.2]octane-based disalts showing non-centrosymmetric structures and phase transition behaviors. Abstract : Two non-centrosymmetric crystals, [(H2 dabco)(H2 O)](ClO4 )2 (1 ; dabco = 1, 4-diazabicyclo[2.2.2]octane) and [(H2 dabco)(H2 O)](BF4 )2 (2 ), were synthesized and characterized, along with their deuterated species [(D2 dabco)(D2 O)](ClO4 )2 (3 ) and [(D2 dabco)(D2 O)](BF4 )2 (4 ). The polar structures are formed by the directional packing of the asymmetric hydrogen-bonded supramolecular unit [(H2 dabco)(H2 O)] and stabilized by hydrogen bonds among the cations and the anions. Meanwhile, these compounds undergo phase transitions in the temperature range of 230–250 K, revealed by differential scanning calorimetry and dielectric constant measurements. Crystal structure analysis and deuteration study indicate that the order–disorder transition of the anions is the main driving force for the phase transitions in1 and2 .